2009
DOI: 10.1152/ajpheart.00116.2009
|View full text |Cite
|
Sign up to set email alerts
|

Periadventitial adipose tissue impairs coronary endothelial function via PKC-β-dependent phosphorylation of nitric oxide synthase

Abstract: Endogenous periadventitial adipose-derived factors have been shown to contribute to coronary vascular regulation by impairing endothelial function through a direct inhibition of endothelial nitric oxide synthase (eNOS). However, our understanding of the underlying mechanisms remains uncertain. Accordingly, this study was designed to test the hypothesis that periadventitial adipose tissue releases agents that attenuate coronary endothelial nitric oxide production via a protein kinase C (PKC)-beta-dependent mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 53 publications
1
69
1
2
Order By: Relevance
“…The other possibility is the direct influence of an enlarged perivascular fat mass on vessel wall dysfunction, as suggested in obesity and type 2 diabetes, 11 in heart disease animal models, 39 and more specifically in the modulation of coronary endothelial function. 8,9 Inflammation, vasoactive adipokines, and mediators secreted locally by IPF could explain our findings. In fact, enlarged adipocytes increase the proportion of macrophages, T lymphocytes, 10 and detrimental adipocytokines, such as leptin, resistin, interleukin 6, and tumor necrosis factor ␣.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The other possibility is the direct influence of an enlarged perivascular fat mass on vessel wall dysfunction, as suggested in obesity and type 2 diabetes, 11 in heart disease animal models, 39 and more specifically in the modulation of coronary endothelial function. 8,9 Inflammation, vasoactive adipokines, and mediators secreted locally by IPF could explain our findings. In fact, enlarged adipocytes increase the proportion of macrophages, T lymphocytes, 10 and detrimental adipocytokines, such as leptin, resistin, interleukin 6, and tumor necrosis factor ␣.…”
Section: Discussionmentioning
confidence: 72%
“…18 -20 The relationship between accumulation of IPF and EPF and myocardial perfusion (MBF) in patients with CAD has not been investigated, although a strong mechanistic link is supported by evidence of vasoactive adipokines released into the coronary lumen. 8,9,21 One group 22 has examined and found a correlation between echocardiographically measured CFR and epicardial fat thickness in women with normal coronary arteries.…”
mentioning
confidence: 99%
“…Of note, endothelial PKCβ activation has been suggested to negatively impact endothelial function and to inhibit eNOSactivating pathways (45)(46)(47)(48).…”
Section: Figurementioning
confidence: 99%
“…Our findings further indicated that increased endothelial PKCβII activation by HDL CAD was involved in the impaired effects of HDL CAD on eNOS-derived NO production and was mediated, at least in part, via the endothelial LOX-1 receptor. Endothelial PKCβ activation has been observed to promote endothelial dysfunction, to inhibit Akt-dependent eNOS-activating phosphorylation at Ser1177, to increase eNOS-inhibiting phosphorylation at Thr495 (45)(46)(47)(48)58), and to promote endothelial inflammatory activation (49).…”
Section: Figurementioning
confidence: 99%
“…4,5, 7 In contrast, PVAT may enhance vascular contractile responses by preventing endothelium-dependent vasodilatation through inhibition of endothelial nitric oxide synthase. 8 Furthermore, PVAT increases the extent of vasoconstriction via generation of contractile superoxide anions, which are released after electric field stimulation from functional reduced nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase in rat mesenteric arteries. 9 Lipoatrophic mice born without white fat tissue have a markedly decreased amount of PVAT accompanied with increased arterial pressure and compromised vascular function.…”
mentioning
confidence: 99%